Postoperative Complications and Impact of Diabetes Mellitus Severity on Revision Total Knee Arthroplasty - Gu, Alex; Wei, Chapman; Robinson, Hannah N.; Sobrio, Shane A.; Liu, Jiabin; Sculco, Thomas P.; Sculco, Peter K. (The Journal of Knee Surgery, 2020)
Total knee arthroplasty (TKA) is a common and effective treatment of knee osteoarthritis. As the amount of TKAs performed increases, so does the number of TKA failures and subsequent revisions. Diabetes mellitus (DM) has been shown to increase complications following orthopaedic procedures. For these reasons, it is important to understand the association between severity of DM and the risk of postoperative adverse events following revision TKA. A retrospective cohort study was conducted using the American College of Surgeons' National Surgical Quality Improvement Program database. Patients who underwent revision TKAs between 2007 and 2016 were identified and recorded as having noninsulin-dependent DM (NIDDM), insulin-dependent DM (IDDM), or no DM. Univariate and multivariate analysis were used to evaluate the incidence of multiple adverse events within 30 days after revision TKA. A total of 13,246 patients who underwent revision TKA were selected (without DM = 10,381 [78.4%]; NIDDM = 1,890 [14.3%]; IDDM = 975 [7.4%]). Patients with NIDDM were found to have an increased risk of developing renal insufficiency and urinary tract infection (UTI) compared with patients without DM, while patients with IDDM were found to have an increased risk of developing 10 of 20 adverse events compared with patients without DM. NIDDM is an independent risk factor for UTI and IDDM is an independent factor for development of three complications compared with no DM. Insulin dependency is an independent factor for septic shock, postoperative blood transfusion, and extended postoperative hospital stay. Relative to patients with NIDDM, those with IDDM have a greater likelihood of developing more adverse perioperative outcomes than patients without DM. Although complication rates remain relatively low, orthopaedic surgeons must consider the implications of diabetes and insulin dependence on patient selection, preoperative risk stratification, and postoperative outcomes.
Keywords: revision; knee; arthroplasty; diabetes mellitus; insulin